1999
DOI: 10.4065/74.7.695
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Failure and Proximal Skeletal Myopathy in a Patient With Primary Sjögren Syndrome

Abstract: Autonomic failure and proximal skeletal myopathy are rare features of the Sjögren syndrome (SS). We describe a 51-year-old woman with primary SS who had development of esophageal dysmotility, urinary retention, severe orthostatism, and skeletal myopathy during a 3-month period after the diagnosis of SS. Her symptoms and signs responded well to corticosteroid therapy. Although dysfunction of the peripheral nervous system has a prevalence rate of 20% in patients with SS, most commonly the nerve dysfunction is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Peripheral neuropathy is an important component of the pathology of Sjogren's syndrome (Sorajja, Poirier et al 1999; Hocevar, Tomsic et al 2003). The trigeminal nerve is one of the most commonly affected cranial nerves in primary Sjogren's syndrome (Gemignani, Marbini et al 1994; Barendregt, van den Bent et al 2001).…”
Section: Neural Regulation Of Lacrimal Gland Function and Its Altmentioning
confidence: 99%
“…Peripheral neuropathy is an important component of the pathology of Sjogren's syndrome (Sorajja, Poirier et al 1999; Hocevar, Tomsic et al 2003). The trigeminal nerve is one of the most commonly affected cranial nerves in primary Sjogren's syndrome (Gemignani, Marbini et al 1994; Barendregt, van den Bent et al 2001).…”
Section: Neural Regulation Of Lacrimal Gland Function and Its Altmentioning
confidence: 99%
“…In fact, approximately two‐thirds of patients with neuropathy from Sjögren's syndrome first note sensory symptoms in the feet. Primarily small‐fiber dysfunction may sometimes account for the sensory symptoms, and autonomic fibers may also be affected 18, 94. The presentation may be asymmetric 18.…”
Section: Causes Of Small‐fiber Neuropathymentioning
confidence: 99%
“…Sorajja et al reported on a patient with recent onset primary SS, who developed myopathy and dysautonomia, manifesting as esophageal dysmotility, urinary retention and severe OH. This unusual constellation of symptoms and signs resolved promptly with steroid treatment [13]. Glucocorticoids were reportedly successful in resolving another case of incapacitating autonomic cardiovascular neuropathy that was the presenting complaint in a patient diagnosed as having primary SS [14].…”
Section: Ans Dysfunction In Ss: Preliminary Uncontrolled Studies and mentioning
confidence: 94%